Efforts to Increase Motivation and Learning Outcomes of Citizenship Education Using the Inside-Outside-Circle Cooperative Learning Model in Grade 6 Students - Muriyanti, Titik (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to increase learning motivation and learning outcomes of Civics using the Inside-Outside-Circle Type Cooperative Learning model in Grade VI students at SDN 1 Sumbung Cepogo Boyolali. This type of research is Classroom Action Research (CAR). The subjects of this study were all 27 students of class VI, totaling 27 students. The instruments used are questionnaires, tests, observation and documentation. The results of this study show that the use of the Inside-Outside-Circle Type Cooperative Learning model can increase the motivation and learning outcomes of Civics students in class VI. This can be seen from the first cycle of student motivation 70.37% in cycle II increased by 88.88%. While the learning outcomes in the pre-action average were 72, in cycle 1 it increased by 66.66% to 70.60%. In cycle II there was an increase of 77.78% so that the class average became 79.87.